Review of the genus Sekaliporus Watts, 1997 with description of a new species from northern Australia (Coleoptera: Dytiscidae, Hydroporinae) - Hendrich, Lars; Balke, Michael (Zootaxa, 2015)
Sekaliporus davidi sp. n. is described from northern Australia. It is the second species in the genus. It occurs from the Kimberley region in the northwest of Western Australia to north-eastern Queensland. The new species is morphologically similar to S. kriegi Watts, 1997 described from the Kakadu area in the Northern Territory but well characterized by its constantly larger size, six yellowish markings on elytra, the different form of the apical triangular spine of elytra, and the form of the median lobe. Sekaliporus davidi sp. n. is a lotic species from intermittent creeks and slow flowing rivers and their residual pools. Important species characters (median lobes, parameres and colour patterns) of the two species are figured, and notes on their habitats and distribution are given. Both species are capable of flight and were also collected at light.